The next challenge for VATS lobectomy surgeons - Martin-Ucar, Antonio E. (Journal of Thoracic Disease, 2014)
Dr. Xu stimulating manuscript (1) shows the progress made in VAT surgery over recent years. The series of patients undergoing bronchial sleeve resections via VATS represent another new challenge for thoracic surgeons in the search for improved outcomes.